2022
DOI: 10.1177/02666669221087184
|View full text |Cite
|
Sign up to set email alerts
|

The influence of accounting information system on management control effectiveness: The perspective of SMEs in Yemen

Abstract: In today’s competitive market, SMEs need to realize that accounting information system (AIS) can enhance management control effectiveness (MCE) - one of the areas necessary for their survival and success. This paper aimed to measure the influence of AIS success on MCE among SMEs of Yemen, a less developed country, as research and knowledge are very limited in such context. Data were collected from 315 SME owners and managers via a questionnaire. SmartPLS 3 software was employed for data analysis. The results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 113 publications
7
42
0
Order By: Relevance
“…Evidence in the IS effectiveness literature also found a positive effect from system quality on both user satisfaction and individual benefits (e.g. Al-Hattami and Kabra, 2022;Al-Adwan et al, 2021;Al-Okaily et al, 2021c;Al-Debei et al, 2013;Almaz an et al, 2017). Thus, we hypothesize:…”
Section: System Qualitymentioning
confidence: 88%
“…Evidence in the IS effectiveness literature also found a positive effect from system quality on both user satisfaction and individual benefits (e.g. Al-Hattami and Kabra, 2022;Al-Adwan et al, 2021;Al-Okaily et al, 2021c;Al-Debei et al, 2013;Almaz an et al, 2017). Thus, we hypothesize:…”
Section: System Qualitymentioning
confidence: 88%
“…Recent research has suggested that using smart software to carry out standardized accounting tasks could decrease the costs of such services and free resources to pay for advisory services are more likely to serve as a resource in the RBV sense and result in competitive advantage (Ma et al , 2021). In addition, further research indicates that more professional computerized accounting systems could help create more effective accounting and control systems in SMEs (Al-Hattami and Kabra, 2022). At the same time, the underlying dynamics have thus far received little research attention.…”
Section: Future Research Avenuesmentioning
confidence: 99%
“…Corporate governance is one of the most often debated topics among academic and industry researchers in the present financial environment [ 26 32 ]. India is one of the countries that constantly monitors global trends in corporate governance and revises its regulatory framework regularly.…”
Section: Theoretical Frameworkmentioning
confidence: 99%